Development of DACAR as a new learning model to train critical and creative thinking skills: A study on early childhood education - Gusmaniarti, Gusmaniarti; Mustaji, Mustaji; Widodo, Wahono; Suryanti, Suryanti; Wiryanto, Wiryanto (Edelweiss Applied Science and Technology, 2025)
This research seeks to evaluate the validity and reliability of the DACAR learning model, an instructional framework incorporating Demonstration, Association, Collaboration, Action, and Reward as an innovative method for fostering critical and creative thinking in early childhood education. The DACAR approach is tailored to support engaging, activity-based learning experiences that align with young children’s developmental traits, such as their curiosity, imagination, and social nature. The model was developed using a research and development (R&D) methodology, which involved model conceptualization, expert validation, reliability testing, and subsequent revisions. Validation of the DACAR model and its associated instruments was conducted by three field-specific experts, while learning tools were assessed by four validators, and reliability testing involved three evaluators. Assessments used a 5-point Likert scale, with additional space for qualitative feedback. The results revealed that the validity coefficients for the DACAR model (rα = 0.997, 0.993, and 0.990) exceeded the critical value of rtable. Similarly, high validity scores were observed for learning plans (RPPH) (rα = 0.983, 0.984, 0.991, 0.989), instructional materials (rα = 0.961, 0.978, 0.997), and implementation evaluations (rα = 0.961, 0.978, 0.997). Instruments measuring children’s activity (rα = 0.90, 0.81, 0.75) and learning observations (rα = 0.857, 0.570, 0.857) also demonstrated acceptable validity, and a learner response score of 3.67 was recorded. Regarding reliability, the DACAR model scored 0.992, while RPPH tools scored 0.990, teaching materials 0.950, implementation tools 0.662, children’s observation sheets 0.761, and response questionnaires 0.907. Based on these findings, the DACAR model is deemed suitable for use as a viable educational strategy to enhance critical and creative thinking in early childhood education.